STRATEGI KELAYAKAN DAN PENINGKATAN MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN UMKM KULINER DI MASA PANDEMI COVID-19. STUDI KASUS: KOTA BANGKINANG, KAMPAR, RIAU: Case Study: Bangkinang City, Kampar, Riau. - Samsurijal Hasan; Kurniawan Adha; Utami Yerikania (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
The Covid-19 pandemic can be classified as a disaster where it not only has a health impact but also has a major impact on the social and economic life of the community. Efforts to reduce the spread of the Covid-19 virus are carried out by restricting people's movements and vaccinations. In this new normal, known as the term Work or Study from Home, this situation also causes changes in the cultural, social, and economic order of the society. This study aims to determine the feasibility of social media as a marketing medium for culinary MSMEs in Bangkinang City and what are the opportunities and challenges for this industry. A study on the marketing effectiveness of online MSMEs for the food or culinary sector in a pandemic was conducted to examine the effectiveness of online media in increasing sales. This basic method is used with income analysis through a survey approach to 6 MSMEs that use digital as a marketing base and responses from 300 respondents. Identification of Internal and External Factors found that the position of internal factors in the development of digital promotion of MSEM Culiner sector in Bangkinang City was still classified in the weak category. This shows that with low effort in digital marketing, it is able to provide good enough feedback and needs to be improved. From the results of mapping the IFE and EFE factors, the strategic position and development of digital promotion of MSME culinary sector in Bangkinang City, Kampar Regency is in Quadrant II, namely the STABILITY quadrant or in a stable condition. From the results of the SWOT analysis, ten strategies are given which are the results of the formulation of internal factors (IFE) and external factors (EFE). The strategy in this study is intended as a plan (planning) to achieve the goal. Strategy as a plan is a planned program or step which are a directed course of action to achieve a set of predetermined goals or ideals, as is the case with the concept of strategic planning.